A new species of Rhipidoglossum (Orchidaceae, Angraecinae) from the Western Rift Valley (Africa) - Arthur Macedo; Marcelo Trovó; Tariq Stévart; João Farminhão (Plant Ecology and Evolution)
Background and aims – Rhipidoglossum is the third most species-rich epiphytic orchid genus in continental Tropical Africa, containing at least 53 species. As part of an ongoing taxonomic revision, a new species endemic to the Western Rift Valley was identified. The novelty was previously confused with R. adoxum and R. globulosocalcaratum. Here, we aim to clarify the diagnostic traits and geographic distribution of these three species. Material and methods – We applied standard herbarium taxonomic practices to a geographically representative sampling of dry and spirit specimens identified as R. adoxum and R. globulosocalcaratum, and conducted a thorough review of regional floras and field photographs to compile all available information on the novelty. A synoptic table, distribution map, and the risk of extinction based on IUCN Red List conservation status accompany the description and illustration of this new species. Key results – Rhipidoglossum fischerianum sp. nov., R. globulosocalcaratum, and R. adoxum can be distinguished from each other based on stem size, leaf apex, perianth, and rostellum morphology. Rhipidoglossum fischerianum is endemic to the lower montane forests in the Western Rift, whereas R. globulosocalcaratum is restricted to the Guineo-Congolian forests, and newly recorded from Cameroon and Uganda. Rhipidoglossum adoxum is found in montane forests of Ethiopia, Kenya, and South Sudan. The new species is preliminarily assessed as Vulnerable (VU). The name R. globulosocalcaratum is here lectotypified. Conclusion – This new species increases the diversity of Rhipidoglossum in the Western Rift to 16 species, of which 10 are endemic or near-endemic to the region. It highlights the relevant role of ongoing taxonomic work and the preservation of the Western Rift forests, which harbour high levels of unique biodiversity.